USING LOCAL TOURISM OBJECT TO TEACH WRITING DESCRIPTIVE TEXT - Chandra Pratama (Journal of English Education Program (JEEP), 2016)
This study was conducted to analyze students’ enthusiasm and perceptions in writing descriptive text by using video. English teacher needs a technique of teaching by using mutimedia such as video. It is expected to help the students study writing and this technique makes the students enjoy following material. The aim of this study is to investigate whether the students is more encouraged to learn descriptive text by means of video and how the students perceive about using video for their writing descriptive text. In collecting the data regarding the research question above, the writer conducted the study by gaining qualitative research with case study as the reseach design applied by the writer.